Validity of deed of declaration as an authentication of ownership: a study with particular reference to post-war resettlement and award of compensation for victims of land in the northern province of sri lanka - Manoharan, K. (University of Jaffna, 2012)
Since people have lost almost all their legal documents during the displacement and calamities of war, proof of ownership to their own land too has become a difficult task. The people who are allowed to resettle in their places of origin need to establish the ownership to the land belonging to them in order to receive housing and various assistance from state and non state agencies. The researcher wants to analyze the possibility of execution of a deed of declaration and get it recognized by the funding or assisting agency. The researcher also intends to analyze the legal and practical barriers in the process of validating and recognizing deeds of declaration as proof for ownership and award of compensation for victims of land in Northern province of Sri Lanka in the post war context. This study will be based on interviews with different stake holders such as Divisional secretaries, Notary publics and the victims of lands etc. It is alleged by the relevant officers that the genuineness of deed of declaration is always doubtful since it is a mere declaration of one’s ownership over a land. The researcher intends to say where and when the deed of declaration could be a genuine document and acceptance of them by the respective officials when they could be treated as genuine. The research finding will hopefully help the people and the respective officers to recognize the validity of the deed of declaration to a good extent to redress the victims.